Exploring the role of iron-solubilizing Bacillus sp. in promoting cereal growth - Hussain, Azhar; Saeed, Maryam; Anwar, Hammad; Dar, Abubakar; Imran, Muhammad; El-Beltagi, Hossam S.; Zulfiqar, Usman; Abdulloev, Obidjon; Rebouh, Nazih Y.; Prasad, P. V. Vara (Frontiers in Microbiology, 2025)
IntroductionIron (Fe), being the most limited micronutrient in soils, performs key functions in a plant’s physiology, namely, enzyme activation and chlorophyll synthesis. Its deficiency prevails in humans in the form of disorders in pregnant women and children, for example, anemia.MethodsTherefore, the current investigation aims at isolating, screening, characterizing, and identifying Fe-solubilizing bacteria and their impact on maize and wheat growth under axenic conditions.ResultsThe results depicted their differential response against siderophores and exopolysaccharide production, urease activity, phosphorus, and zinc solubilization. Under axenic conditions, the maximum increase in wheat shoot, root length, chlorophyll a, chlorophyll b, and carotenoid contents under AH-22 isolates was observed, which showed an increase of 67.2, 34.6, 24.7, 30.1, and 41.7%, respectively, compared to the control. Similarly, maximum increase of 41.8, 41.7, 37.2, 37, and 16.4%, respectively, was recorded in maize shoot and root lengths, chlorophyll a, chlorophyll b, and carotenoid contents under AH-34 strain inoculated treatment. Furthermore, the molecular identification of the promising rhizobacteria revealed that AH-22 was identified as Bacillus subtilis, AH-26, AH-36, AH-46 as Bacillus sp., and AH-34 as a Bacillus megaterium strain.DiscussionOn the basis of the revealed results, it can be concluded that rhizobacterial strains B. subtilis (AH-22) in wheat and B. megaterium (AH-34) in maize effectively enhanced wheat and maize growth by improving nutrient solubilization and physiological traits. Moreover, the studied strains need to be tested in natural field conditions, and the development of certain formulations to boost growth and Fe-biofortification in cereals.